Systems engineering : fifty lessons learned - Eisner, Howard, 1935- (Boca Raton, FL : CRC Press, 2020)
"This Focus book provides a "looking back" at author's 50-year run and the lessons he learned and would like to share with other engineers, so they can use these lessons in their day-to-day work in systems engineering and related fields. The book is written from a systems engineering perspective. It offers 50 lessons learned while the author worked for a variety of different companies, which can be used across many other engineering fields"--
OCLC-licensed vendor bibliographic record.
Keywords: Systems engineering -- Management; TECHNOLOGY / Manufacturing; BUSINESS & ECONOMICS / Project Management